Anticholinesterase and antioxidant activities of fucoxanthin purified from the microalga Phaeodactylum tricornutum - Arthitaya Kawee-ai (2018)
Hot extraction with acetone was the most efficient method for the extraction of fucoxanthin from Phaeodactylum tricornutum. The purified compound resulted in three main peaks consisted of the trans form along with two isomers. The structure of microalgal fucoxanthin was similar to that of brown seaweed, but the ratio of trans- to cis-form was different. The ratio of the cis-form increased as the extraction temperature increased. Fucoxanthin was unstable at high temperature, in acidic condition, and after long period of storage. Fucoxanthin exhibited strong activity against BChE, with an IC 50 value of 1.97 mM and mixed inhibition type, whereas it had weak activity against AChE. The IC 50 value on reducing power was 0.01 mM, which was much stronger than those of the positive controls. When the amount of cis-isomer increased by 2%, the scavenging activity against DPPH, hydrogen peroxide, superoxide anion, and reducing power decreased by 21.0, 10.3, 16.0, and 19.7%, respectively. Therefore, fucoxanthin could be a useful approach for Alzheimer's disease treatment.